Comparison of imaging biomarkers for Alzheimer's disease: amyloid imaging with [18F]florbetapir positron emission tomography and magnetic resonance imaging voxel‐based analysis for entorhinal cortex atrophy. (7th July 2014) - Tateno, Amane; Sakayori, Takeshi; Kawashima, Yoshitaka; Higuchi, Makoto; Suhara, Tetsuya; Mizumura, Sunao; Mintun, Mark A.; Skovronsky, Daniel M.; Honjo, Kazuyoshi; Ishihara, Keiichi; Kumita, Shinichiro; Suzuki, Hidenori; et al.
<x xml:space="preserve">Abstract</x> Objective We compared amyloid positron emission tomography (PET) and magnetic resonance imaging (MRI) in subjects clinically diagnosed with Alzheimer's disease (AD), mild cognitive impairment (MCI), and older healthy controls (OHC) in order to test how these imaging biomarkers represent cognitive decline in AD. Methods Fifteen OHC, 19 patients with MCI, and 19 patients with AD were examined by [18F]florbetapir PET to quantify the standard uptake value ratio (SUVR) as the degree of amyloid accumulation, by MRI and the voxel‐based specific regional analysis system for AD to calculate z‐score as the degree of entorhinal cortex atrophy, and by mini‐mental state examination (MMSE) and Alzheimer's Disease Assessment Scale–cognitive component—Japanese version (ADAS‐Jcog) for cognitive functions. Results Both cutoff values for measuring AD‐like levels of amyloid (1.099 for SUVR) and entorhinal cortex atrophy (1.60 for z‐score) were well differentially diagnosed and clinically defined AD from OHC (84.2% for SUVR and 86.7% for z‐score). Subgroup analysis based on beta‐amyloid positivity revealed that z‐score significantly correlated with MMSE (r = −0.626, p < 0.01) and ADAS‐Jcog (r = 0.691, p < 0.01) only among subjects with beta‐amyloid. Conclusions This is the first study to compare [18F]florbetapir PET and MRI voxel‐based analysis of entorhinal cortex atrophy for AD. Both [18F]florbetapir PET and MRI detected changes in AD compared with OHC. Considering that entorhinal cortex atrophy correlated well with cognitive decline only among subjects with beta‐amyloid, [18F]florbetapir PET makes it possible to detect AD pathology in the early stage, whereas MRI morphometry for subjects with beta‐amyloid provides a good biomarker to assess the severity of AD in the later stage. Copyright © 2014 John Wiley & Sons, Ltd.